The correlates of work in a post-AFDC world: the results from a longitudinal state-level analysis - Dan Lewis; Spyros Konstantopoulos; Lisa Altenbernd (Institute for the Study of Labor (IZA), 2005)
Much of the research that has followed welfare reform and new policies such as the Temporary Assistance for Needy Families (TANF) has focused on identifying the variations in how different states have put the new policy into practice. Less is known however, about how this new policy affects the ability of recipients to earn a living through work. We use panel data from the state of Illinois and examine what explains labor force participation and performance among current and recent TANF recipients. We use both cross-sectional and longitudinal methods to analyze our data. Our results indicate that human capital factors such as education, job skills, and health are important determinants of labor market participation and performance. In addition, we find that long term welfare recipients are equally likely to participate and perform well in the labor market as shorter term welfare recipients. Finally, government housing subsidy appeared to have a positive effect on labor force participation and performance.
Keywords: I38; J20; J24; J30; 330; welfare; employment; earnings